Rheological properties of cement pastes with cellulose microfibers - Seongwoo Gwon; Myoungsu Shin (Journal of Materials Research and Technology, 2021)
The rheological properties of cement pastes prepared using kenaf-plant cellulose microfibers (CMFs), which was incorporated for the purpose of internal curing, were investigated. The main test variables are the length and mass fraction of the CMFs. CMFs of lengths of 400 μm and 5 mm were included in the mixtures at 0.3, 0.6, 1, and 2 wt.% of the cement. Dry CMF particles were wetted with water to the fiber saturation point using vacuum filtration immediately before mixing. An optimum shearing protocol was designed to minimize the shear-induced structural breakdown of cement pastes with the CMFs under hysteresis loops of the shear strain rate. It consisted of an initial pre-shearing step at a high shear strain rate of 80 1/s, three acceleration and deceleration cycles with a maximum shear strain rate of 40 1/s, and a rest step before each acceleration. The mixtures’ flow curves were well fitted to the Herschel–Bulkley fluid model with a minimum coefficient of determination of 0.9993. The yield stress of cement pastes was at least 34.3% higher for longer CMFs at the same dose. However, the mixtures exhibited similar plastic viscosities with a coefficient of variation of only approximately 5.8%.